THE MOST FUNDAMENTAL EDUCATION CONFLICT IN INDONESIA: A SYSTEMATIC LITERATURE REVIEW - Naibaho, Frainskoy Rio (Sanata Dharma University Yogyakarta, 2023)
This paper aims to investigate the main issues in education in Indonesia and propose sustainable solutions so that education policymakers, stakeholders, and academics can increase their awareness and knowledge of the education conflict. This paper systematically reviews the literature on educational conflicts in Indonesia from 2000 to 2021. The journals used as the main reference in this study are quality journals indexed by Scopus. The literature sources were obtained from a trusted institution called Taylor Francis Online. This institution is located in the UK and is a well-known multinational company publishing books and academic journals. Several issues are found in the literature, but the crucial issues that are most often discussed and need serious attention in the literature are the limited number of skilled teachers, inadequate facilities and infrastructure, lack of learning materials, high cost of education, low quality of education, and the minority of disabled groups.